An easy to assemble PDMS/CNTs/PANI flexible supercapacitor with high energy-to-power density. Issue 6 (26th January 2022) - Balboni, Raphael D. C.; Maron, Guilherme K.; Masteghin, Mateus G.; Tas, Mehmet O.; Rodrigues, Lucas S.; Gehrke, Veridiana; Alano, José H.; Andreazza, Robson; Carreño, Neftali L. V.; Silva, S. Ravi P.
Abstract : PDMS is used as matrix to produce a flexible supercapacitor based on aligned carbon nanotubes and polyaniline, which presents outstanding energy-to-power density ratio and remarkable cycling stability even at different bending angles. Abstract : The fabrication of a flexible supercapacitor with state-of-the-art performance is described, based on a facile and low-cost fabrication method that encompasses aligned carbon nanotube arrays (ACNTA)-polyaniline/polydimethylsiloxane electrodes (ACNTA-PANI/PDMS). The ACNTA were partially embedded in PDMS to ensure excellent adhesion and integration whilst PANI was electrodeposited on its surface to improve energy storage properties. The supercapacitor structure and morphology were investigated by Raman spectroscopy and scanning electron microscopy (SEM), respectively. The energy storage properties of the electrodes were evaluated in two and three-electrode configurations. The maximum value of specific capacitance was 408 mF cm −2 (265 F g −1 ) at 1 mA cm −2, and a high energy density of 20 μW h cm −2 (25.5 W h kg −1 ) was achieved at a power density of 100 μW cm −2 (126.6 W kg −1 ) for a symmetric two-electrode device. The device showed a good capacitance retention of 76% after 5000 cycles and was able to maintain 80% of its electrochemical properties while being measured at different bending angles, demonstrating excellent mechanical agility performance under extreme conditions and some of the highest carbon-based energy storage properties.